2021
DOI: 10.1007/s12665-021-10047-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the physical properties of natural sedimentary loess and manual filling compacted loess

Abstract: With the development of human society, mega engineering projects of removing the tops of hills to in ll valleys began to appear in the loess region. The thickness of the manual lling compacted loess can reach tens of meters. For such large-scale construction projects, studying the properties of compacted loess is essential to ensure the safety and reliability of land creation and arti cial infrastructure. In this paper, the specimens from two exploration well pro les were carried out to study the physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Therefore, relevant experimental studies and analyses are urgently needed. By comparing the physical properties of naturally deposited loess and compacted loess, Zhang et al [26] found that the liquid limit, plastic limit, plasticity index, clay fraction, silt fraction, sand fraction, and compression modulus of the compacted loess were smaller, and it was more prone to deformation under external forces.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, relevant experimental studies and analyses are urgently needed. By comparing the physical properties of naturally deposited loess and compacted loess, Zhang et al [26] found that the liquid limit, plastic limit, plasticity index, clay fraction, silt fraction, sand fraction, and compression modulus of the compacted loess were smaller, and it was more prone to deformation under external forces.…”
Section: Introductionmentioning
confidence: 99%
“…When the flow path changes, the solute flux also changes [ 6 , 13 ]. In disturbed conditions, soil disturbance can damage the soil structure [ 14 ], expose minerals, and change the water flow path [ 6 ]. Therefore, the mechanisms of the water–rock interaction are the key to understanding the influence of water–rock interactions on water chemistry and the evolution of solutes.…”
Section: Introductionmentioning
confidence: 99%